2019
DOI: 10.2478/acph-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial assesment of aroylhydrazone derivatives in vitro

Abstract: Aroylhydrazones 1–13 were screened for antimicrobial and antibiofilm activities in vitro. N′-(2-hydroxy-phenylmethylidene)-3-pyridinecarbohydrazide (2), N′-(5-chloro-2-hydroxyphenyl-methylidene)-3-pyridinecarbohydrazide (10), N′-(3,5-chloro-2-hydroxyphenylmethylidene)-3-pyridinecarbohydrazide (11), and N′-(2-hydroxy-5-nitrophenylmethylidene)-3-pyridinecarbohydrazide (12) showed antibacterial activity against Escherichia coli, with MIC values (in µmol mL−1) of 0.18–0.23, 0.11–0.20, 0.16–0.17 and 0.35–0.37, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Antibacterial assays performed in this study showed that compound 17 with nitro group displayed good inhibition of bacterial growth, whereas the compounds without an electron-withdrawing group (chloroand nitro-) showed weak antibacterial activity (Figure 11, Table 5). According to the authors, this may be due to the fact that electron-withdrawing substituents increase the lipophilicity of the compounds, which leads to higher partitioning of such compounds into the lipophilic phase of a microbial membrane [22]. 6, Figure 12) [23].…”
Section: Antimicrobial Activity 21 Antibacterial Activitymentioning
confidence: 99%
“…Antibacterial assays performed in this study showed that compound 17 with nitro group displayed good inhibition of bacterial growth, whereas the compounds without an electron-withdrawing group (chloroand nitro-) showed weak antibacterial activity (Figure 11, Table 5). According to the authors, this may be due to the fact that electron-withdrawing substituents increase the lipophilicity of the compounds, which leads to higher partitioning of such compounds into the lipophilic phase of a microbial membrane [22]. 6, Figure 12) [23].…”
Section: Antimicrobial Activity 21 Antibacterial Activitymentioning
confidence: 99%
“…Among them, hydrazine-, hydrazone-, and isothiocyanate-based compounds are found to have various applications in organic synthesis, medicinal chemistry, combinatorial chemistry, and supramolecular chemistry. Concerning organic synthesis, such compounds were proved to participate in the construction of different heterocyclic scaffold classes such as azetidines, coumarins, oxadiazolines, diazoles, triazoles, quinazolines, thiazolidines benzothiazines, and triazoloquinazolines. Their distinct biological significance was explained on the basis of the specific structural combination for a (−NH–NCH−) or (N–N) group with a carbonyl or thiocarbonyl group and their reactivities toward both electrophiles and nucleophiles. Therefore, they are present in many bioactive compounds and demonstrate a wide variety of biological activities including anticancer, antioxidant, antimicrobial, antifungal, anti-inflammatory, anticonvulsant, antiviral, and antiprotozoal effects. The process of discovering antioxidants has been gaining growing interest due to their valuable protective roles in both pharmaceutical and food industries. In human physiology, they play an essential role against oxidative deterioration and oxidative stress-mediated mechanisms, whereas in the food system, antioxidants retard lipid peroxidation, prevent the formation of secondary lipid peroxidation products, maintain the flavor, color, and texture of the food product during storage, and reduce the interaction of lipid-derived carbonyls with proteins that is accompanied by alteration in protein function. , There has been renewed interest to explore new antioxidant molecules either synthetically or naturally, so as to utilize them as the main agents to counter toxicity mediated by radicals.…”
Section: Introductionmentioning
confidence: 99%